Molecular and Clinical Features of Non-Burkitt’s, Diffuse Large-Cell Lymphoma of B-Cell Type Associated With the c-MYC/Immunoglobulin Heavy-Chain Fusion Gene - Akasaka, Takashi; Akasaka, Hiroshi; Ueda, Chiyoko; Yonetani, Noboru; Maesako, Yoshitomo; Shimizu, Akira; Yamabe, Hirohiko; Fukuhara, Shirou; Uchiyama, Takashi; Ohno, Hitoshi (Journal of clinical oncology, 2000)
PURPOSE: t(8;14)(q24;q32) and/or c-MYC/immunoglobulin heavy-chain (IGH) fusion gene have been observed not only in Burkitt’s lymphoma (BL) but also in a proportion of non-BL, diffuse large-cell lymphoma of B-cell type (DLCL). We explored molecular features of DLCL with c-MYC/IGH fusion and the impact of this genetic abnormality on clinical outcome of DLCL. PATIENTS AND METHODS: A total of 203 cases of non-BL DLCL were studied. Genomic DNA extracted from tumor tissues was subjected to long-distance polymerase chain reaction (LD-PCR) using oligonucleotide primers for exon 2 of c-MYC and for the four constant region genes of IGH. RESULTS: Twelve cases (5.9%) showed positive amplification; one had a c-MYC/Cμ, nine had a c-MYC/Cγ, and two had a c-MYC/Cα fusion sequence. Restriction and sequence analysis of the LD-PCR products, ranging from 2.3 to 9.4 kb in size, showed that breakage in the 12 cases occurred within a 1.5-kb region that included exon 1 of c-MYC in combination with breakpoints at the switch regions of IGH (10 of 12). In 10 cases, Myc protein encoded by the fusion genes demonstrated mutations and/or deletions. Six cases had additional molecular lesions in BCL-2 or BCL-6 and/or p53 genes. The age range of the 12 patients was 44 to 86 years, with a median age of 65.5 years. Five patients had stage I/II disease, and seven had stage III/IV disease. Lactate dehydrogenase was elevated in nine of 11 subjects. Seven showed involvement of the gastrointestinal tract. All patients were treated by surgery and/or chemoradiotherapy; six died of the disease within 1 year, resulting in the poorest 1- and 2-year survival rates among DLCL subgroups. CONCLUSION: The c-MYC/IGH fusion gene of DLCL is identical to that of the sporadic type of BL (sBL). DLCL with c-MYC/IGH shares clinical features with sBL but is characterized further by an older age distribution.